MENINGKATKAN PRESTASI BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT(TGT) PADA PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK DI KELAS XI-D SMAN 1 ADONARA - Gerardis Mayela Barek Bala; Ignasia Yovita Kuna Koten (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The purpose of this study is to determine the improvement of learning achievement of students in grades XI-D at SMA Negeri 1 Adonara in PAK subjects through a cooperative learning model of the team games tournament (TGT) type. This study uses a type of classroom action research with a descriptive qualitative approach. Classroom action research was carried out at SMAN 1 Adonara in classes XI-D or FD Phase by going through two cycles, namely cycle I was carried out on September 23, 2024 and cycle II on September 30, 2024. The results of the study showed that there was an increase in learning achievement, namely in the cognitive, affective, and psychometric aspects. The results obtained in the pre-cycle stage obtained the class average of learning outcomes or learning achievement of 61.40, cycle I of 65.33, and cycle II of 83.60. Meanwhile, the increase in presentations from each cycle for students who reach the Minimum Achievement Criteria (KKM) set by the school for the Catholic Religious Education subject is 75. In the pre-cycle of 20%, Cycle I is 33% and Cycle II is 100%. Thus, the application of the cooperative learning model of the team games tournament type can increase the learning achievement of students in SMAN 1 Adonara class XI-D or the FD phase.